Jump [videorecording (DVD)]. - Burley, Nichola, 1986-; McCann, Martin, 1983-
Follows the trials and tribulations of three seemingly unconnected sets of young people in Belfast on New Year's Eve. Gradually, the links between them are revealed as fate takes a hand in a night of fast talk, accidents and intrigue.